2018
DOI: 10.1186/s12935-018-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and clinicopathological features of the IL-33/ST2 axis in human esophageal squamous cell carcinomas

Abstract: BackgroundEmerging evidence has suggested that interleukin (IL)-33 and its primary functional receptor ST2 are involved in the pathogenesis of tumorigenesis.MethodsUsing immunohistochemistry (IHC) and double immunofluorescence staining, we characterized the cellular and clinicopathological features of the IL-33/ST2 axis in different compartments in human esophageal squamous cell carcinoma (ESCC) surgical specimens.ResultsIHC data revealed an increased expression of IL-33-immunoreactivity (IR) and ST2-IR locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Studies on several malignancies (including renal cancer) suggest that the IL33/IL33Rα axis could be important in tumorigenesis through exerting direct effects on malignant cells [ 64 ] or indirectly through effects on stromal cells [ 65 ], including altering the regulation of tumor angiogenesis [ 66 ]. An association between serum IL33Rα levels and prognosis has been described for patients with hepatocellular carcinoma [ 67 ] and breast cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on several malignancies (including renal cancer) suggest that the IL33/IL33Rα axis could be important in tumorigenesis through exerting direct effects on malignant cells [ 64 ] or indirectly through effects on stromal cells [ 65 ], including altering the regulation of tumor angiogenesis [ 66 ]. An association between serum IL33Rα levels and prognosis has been described for patients with hepatocellular carcinoma [ 67 ] and breast cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hollande et al found that IL‐33 was essential and active for eosinophil‐mediated antitumor responses. Cui et al observed that the IL‐33/ST2 axis might be involved in the progression of human ESCC. However, the molecular mechanism of IL‐33 in ESCC development remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…IL-33/ST2 axis was involved in the activity of mast cells during colitis, and IL-33 promoted the percentage of IL-13/IL-22 producing T cells, which indicated that IL-33 regulated T cell differentiation and function [24]. In addition, IL-33/ST2 axis was involved in the proliferation of ESCC cells and stromal cells, and the IL-33 or ST2 positive cells in ESCC stroma were positively related to node involvement, invasion depth and TNM stage [25]. Importantly, IL-33/ST2 axis was involved in the regulation of myocardial cell apoptosis [5,6].…”
Section: Discussionmentioning
confidence: 92%